Risk Analysis for insecticide residues in confectionery sunflower for human consumption - Aguilar, Roxana; Cristos, Diego Sebastian; Rodriguez, María S.; Nassetta, M.; Martinez, Maria Jose (Universidad Católica Argentina (UCA), 2025)
Poster